136 incredible coincidences = 136 kebetulan yang menakjubkan / Vikas Khatri ; alih bahasa, Helen Ishwara ; penyunting, L.R. Supriyapto Yahya - VIKAS KHATRI; Helen Ishwara; Supriyapto Yahya, L.R. (Intisari Mediatama, 2007)
144 hlm. : ilus. ; 19 cm